SISTEM INFORMASI PENGLOLAAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN MODEL WATERFALL PADA CV. GINNOZU CIPTA KOMUNIKASI - Solecha, Kusmayanti (www.bsi.ac.id, 2019)
CV Ginnozu Cipta Komunikasi is a manufacturing company engaged in the furniture or interio industry. Raw Material Inventory Management System is one of the most important managerial functions in operations in CV Ginnozu Cipta Communication Besides being an investment that requires a very large capital, Inventory Management System can affect customer service and production functions, marketing functions and financial functions in CV Ginnozu Cipta Communications Inventories of raw materials aim to expedite production activities. CV Ginnozu Cipta Komunikasi does not have a computerized system that can support the needs of raw material management to improve the efficiency and effectiveness of the company, especially in the warehouse. This research was conducted using the waterfall model through the stages of software requirements analysis, design, code generation and testing. This research was conducted with the aim of being able to provide information about the master of goods, transactions and reports based on a certain period in order to facilitate decision making related to raw material inventory management activities.